Building resilience for sexual and reproductive health at the community level: learning from three crisis-affected provinces in Pakistan. Issue 9 (29th September 2022) - Tanabe, Mihoko; Hynes, Michelle; Rizvi, Anjum; Goswami, Nimisha; Mahmood, Nadeem; Krause, Sandra
Abstract : Pakistan regularly faces natural disasters and has a longstanding disaster risk management infrastructure. It is also a nation with high maternal and newborn mortality. Rahnuma-Family Planning Association of Pakistan, with support from the US Centers for Disease Control and Prevention, the Women's Refugee Commission and the International Planned Parenthood Federation South Asia Region's Sexual and Reproductive Health Programme in Crisis and Post Crisis Situations Initiative, embarked on building community capacity to prepare for and respond to sexual and reproductive health (SRH) risks in select disaster-prone areas in Pakistan, and linking communities to existing disaster risk management structures at national, regional and district levels. The initiative began with a training of trainers at the national level, which was cascaded to six union councils (UCs) in three districts in Khyber-Pakhtunkhwa, Punjab and Sindh provinces. Participants developed action plans for their respective UCs that addressed gaps in implementing the Minimum Initial Service Package (MISP) for SRH, the international standard of care for SRH in emergency settings. Communities spent 1.5 years implementing their action plans to strengthen their capacity to respond to SRH needs in the event of an emergency. Project learning highlights the benefits of investing in preparedness to strengthen core services and linking communities to existing formal structures. Action planning led to immediate gains and longer-term benefits. The MISP for SRH was integrated into disaster risk management at all levels. Community mobilisation, awareness raising and the creation of blood donor groups and emergency transport contributed to averting mortality at the community level.